2004
DOI: 10.1016/j.ctrv.2004.06.001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of parental cancer on children and the family: a review of the literature

Abstract: While quantitative studies reported especially disturbed emotional functioning, qualitative studies reported problems in all domains of child functioning. Well-designed studies are needed to gain more insight into the psychosocial functioning of children of cancer patients in order to develop tailored care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
308
1
47

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(373 citation statements)
references
References 43 publications
10
308
1
47
Order By: Relevance
“…The literature shows that both children and adolescents have increased personal responsibilities, resulting in a decrease in social activity and subsequent loss of childhood at a time when peer groups are essential for social development (4,10,14,17). Adolescent truancy rates increase and overall attendance decreases as they need to care for their younger siblings or pick-up extra work shifts to help combat the financial burden cancer puts on a household (11,13).…”
Section: Role Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature shows that both children and adolescents have increased personal responsibilities, resulting in a decrease in social activity and subsequent loss of childhood at a time when peer groups are essential for social development (4,10,14,17). Adolescent truancy rates increase and overall attendance decreases as they need to care for their younger siblings or pick-up extra work shifts to help combat the financial burden cancer puts on a household (11,13).…”
Section: Role Changesmentioning
confidence: 99%
“…A daily routine is an important part of life for preschoolers, grade-schoolers, and adolescents for both structural stability and social behavior guidance (7,11). A parental cancer diagnosis can disrupt the daily routine or schedule due to frequent clinic visits, unexpected hospital admission, and the home turning into a place of care (9,12,13).…”
Section: Daily Routinementioning
confidence: 99%
See 1 more Smart Citation
“…The process of cell death is called apoptosis; if apoptosis does not occur, cancer may develop. Apoptosis is not necessarily a result of DNA damage or mutations [2]. Unlike normal cells, cancer cells do not undergo apoptosis, and they continue to grow and divide irrepressibly.…”
Section: Introductionmentioning
confidence: 99%
“…Even though Malaysia recorded lower number of children, the ratio was higher at 2.5 children per household (Banci Penduduk dan Perumahan Malaysia, Jabatan Perangkaan, 2013). Visser et al (2004), Visser et al (2007), Osborne (2007) and Edwards et al (2008) reported that parental cancer had a range of consequences from the aspect of children's functioning and psychosocial difficulties. Anxiety, fear and uncertainty were common emotional distresses (Kornreich et al, 2008;Fourie, 2008;Buchwald, 2007;Watson, 2006).…”
mentioning
confidence: 99%